Uncertainty and imprecision in decision making and decision support : cross-fertilization, new models and applications : Selected papers from BOS-2016 and IWIFSGN-2016 held on October 12-14, 2016 in Warsaw, Poland /: cross-fertilization, new models and applications : Selected papers from BOS-2016 and IWIFSGN-2016 held on October 12-14, 2016 in Warsaw, Poland. ([2018]) - Unknown
No abstract available